Women, employment and marriage a case study on Tamil working women in urban Seremban / Sharmala Devi R. Renganathan - Sharmala Devi , R. Renganathan (1988)
This is a case study based in urban Seremban. The aim of this study is to look into the situation of Tamil working women from a Hindu background, to see the changes in the women's attitudes, values and behaviour towards marriage. It is divided into five chapters, all of which are based on the fieldwork conducted from the 10th of April to the 15th of May. Below is a brief outline of the various chapters. Chapter one gives a general introduction of the objective and significance of this study. It also discusses the research methodology, the problems encountered during the fieldwork. The concept of women in work, concept of marriage and the profile of the traditional Hindu woman. Chapter two gives various customs in marriage, wedding ceremony. Chapter three discusses about women's attitude towards marriage in areas like age at first marriage, type of marriage, criteria for selection in marriage relationship before marriage and the customs in marriage today. Chapter four discusses about the married life of the Indian women. We look at the type of family she likes to form after marriage, family planning, the size of the family, authority patterns in family, housework and finally, her views on divorce. Chapter five gives a conclusion of this study.